Ustekinumab successfully treated a patient with severe psoriasis vulgaris with primary failure to infliximab and secondary failure to adalimumab - Chiharu Tateishi; Hisayoshi Imanishi; Kulsupa Nimmannitya; Daisuke Tsuruta (Our Dermatology Online, 2015)
Biologic drugs have been recently used to treat psoriasis. However, some patients do not respond or lose therapeutic benefit with first-line use of tumor necrosis factor (TNF) antagonists. We report a case of psoriasis vulgaris, that failed to respond to TNF antagonists, infliximab and adalimumab, completely disappeared after treatment with ustekinumab, a therapeutic agent for biologically blocking p40 protein of interleukin (IL) 12 and 23. This report highlights anti-TNF agents only inhibited the TNF-α/inducible nitric oxide synthase (iNOS)-producing dendritic cells (TIP-DCs), but the plasmacytoid-DC-derived psoriatic response was re-initiated. On the other hand, ustekinumab may inhibit both the TIP-DCs and the plasmacytoid-DC-derived inflammatory response.